How to manipulate droplet jetting from needle type jet dispensers - Phung, Thanh Huy (Sci Rep, 2019)
The needle-type inkjet dispenser has been widely used for various research and industrial purposes. The droplet jetting from the dispenser is closely related to the needle motion, which strikes against the nozzle seat. The strike of the needle on the nozzle seat often cause additional impact due to the bounce back, which may produce multiple droplets per jetting trigger. However, the needle motion is difficult to measure, and the actual behaviors have been known little. In this study, we measured the needle motion using an accelerometer and visualized jetting images to understand jetting behavior in relation to the needle motion. Then, we investigated various parameter effects on needle motion and jetting behaviors based on our proposed measurement methods. From the experimental results, we found that needle travel distance should be in the optimal range in order to produce single droplet per jetting trigger. In conclusion, we proposed an effective parameter selection method for the optimal jetting based on understanding of the jetting physics.